Pelaksanaan Program Deteksi Dini Kanker Cerviks (Ca Cervix) dengan Metode Inspeksi Visual Asam Asetat (IVA) di Kabupaten Kampar - satiti rahayu; Donel Suhaimi; Jasrida Yunita; Zainal Abidin; Syamsul Bahri Riva'i (Jurnal Kesehatan Komunitas, 2018)
ABSTRACT Implementation of early detection of cervical cancer with IVA method is a policy of the Government of the Republic of Indonesia in an effort to anticipate and reduce the incidence of cervical cancer. The low coverage of early detection of cervical cancer in 2016 in Kampar district is only 1,165 women of childbearing age (wus) from the target number of 110,236 people or only 6% of the target 100%. The purpose of this research is to know how the implementation of early detection program of cervical cancer with IVA method. The research method used is qualitative method with narrative research. Data analysis is done is content analysis with Triangulation. Informants in this study amounted to 12 people. The results showed that the implementation of early detection program of cervical cancer with IVA method has been implemented but not yet maximal. Implementation of the program is carried out by Puskesmas and posyandu and midwife as executive staff only 31 people who have been trained. Financing for early detection of cervical cancer is in the burden on the Fund Operasinal Health Assistance Puskesmas and National Health Insurance fund. Midwives as executors have worked according to the SOP that is set although still not maximal due to the limited facilities available. The role of linear sector well vertical and horizontal is good enough. Level of knowledge about cervical cancer is low, shame, fear and worry of WUS as the target IVA is a constraint that is still in encounter and must be in tackling.